PENGEMBANGAN MEDIA ALBUM BUDAYA NUSANTARA PADA MATERI KEBERAGAMAN BUDAYA SDN 6 WONOSARI, GORONTALO - Aprianti, Delfi; Pomalingo, Samsi; Ismail, Reska Putri (SINERGI : Jurnal Riset Ilmiah, 2025)
This research aims to develop cultural album media on cultural diversity material at SDN 6 Wonosari. Learning in schools is inadequate and there is no educative learning media, so far learning has only been based on book texts or student books so that with these problems it is necessary to carry out research into the development of Indonesian cultural album media. The aim of this research is to develop learning media and test the feasibility of the Archipelago Culture Album learning media on cultural diversity material for fourth grade elementary school students. This development research uses a 4D model (Define, Design, Development, Disseminate). To test the suitability of the Indonesian cultural album media, validation was carried out by a team of experts. Data collection uses instruments in the form of questionnaires, interviews, observation sheets and documentation. The Nusantara Culture Album media contains content on Indonesia's cultural diversity which includes traditional clothing, traditional houses, traditional dances and regional specialties. The research results showed that the feasibility level of media experts was 97.7% (very feasible), material experts were 100% (very feasible), user experts were 95.8% (very good). Thus, the percentage obtained by recapitulating the average percentage value is 97.87%. Based on these results, it can be concluded that the Archipelago Cultural Album media developed is feasible and effective for use as a learning medium in increasing students' understanding of Indonesia's cultural diversity in class IV elementary schools.